2004
DOI: 10.12968/bjcn.2004.9.sup1.12495
|View full text |Cite
|
Sign up to set email alerts
|

Defined and refined: criteria for identifying wound infection revisited

Abstract: Clinical criteria for the identification of wound infection are regularly based on a list created by Cutting and Harding (1994). This list was established from empirical data generated in a large, multidisciplinary clinical practice, and is now widely accepted as a seminal article in wound care. Both Cutting (1998) and Gardner et al (2001) have conducted validation exercises on these wound infection criteria, based on the assumption that the criteria broadly apply to most wound types. Although many of the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(126 citation statements)
references
References 20 publications
2
121
0
3
Order By: Relevance
“…The implication is that, most wounds will be infected with Gram positive bacteria since they form the major commensals of the skin. This agrees with previous study of Cutting and White (2004), who reported that pathogens that infect the wound are primarily grampositive bacteria such as methicillin-resistant Staphylococcus aureus (MRSA) and gram-negative Tesfahunegu et al, 2009;Gedebou et al, 1987). Similar results have been obtained in Ghana (Newman et al, 2006), Nigeria (Okesola and Oni, 2000) and Uganda (Anguzu and Olila, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The implication is that, most wounds will be infected with Gram positive bacteria since they form the major commensals of the skin. This agrees with previous study of Cutting and White (2004), who reported that pathogens that infect the wound are primarily grampositive bacteria such as methicillin-resistant Staphylococcus aureus (MRSA) and gram-negative Tesfahunegu et al, 2009;Gedebou et al, 1987). Similar results have been obtained in Ghana (Newman et al, 2006), Nigeria (Okesola and Oni, 2000) and Uganda (Anguzu and Olila, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…However, these symptoms may intense when SSI occur [3]. Furthermore, SSIs are associated with redness, heat, pain, swelling, hyperthermia as temperature greater than 38 degrees centigrade, purulent discharge, and abscess or cellulitis directly related to the surgical site [23]. Moreover, in Sweden, a study conducted to evaluate quality of life of patients with sternal wound infection after cardiac surgery, it was found that if those patients survive, SSI is a very serious complication that negatively impact their quality of life [24].…”
Section: Nurses' Knowledge and Surgical Site Infections: Signs And Symentioning
confidence: 99%
“…These characteristics are sometimes referred to collectively as the signs and symptoms of critical colonisation. 212,213 DOI: 10.3310/pgfar04130 PROGRAMME GRANTS FOR APPLIED RESEARCH 2016 VOL. 4 NO.…”
Section: Introductionmentioning
confidence: 99%